Experimental and theoretical studies on coordination of a flexible cyclohexane based C3-symmetric tripodal ligand with iron, aluminum and gallium. (1st January 2023) - Thakur, Monika; Baral, Minati; Kanungo, B.K.
Graphical abstract: A quinolinol and cis, cis -1, 3, 5-tris(amino)cyclohexane-based tripodal ligand has been designed, synthesized, characterized. The solution studies have been undertaken through potentiometric, absorption and emission spectroscopy separately for ligand and their metal complexes. The experimental outcomes, structure and bonding are established by computational algorithm by DFT. Abstract: The use of a cyclohexane ring in the centre of a C3 symmetric tripodal ligand with a suitable spacer can flip between the axial and equatorial forms due to low transition energy and can facilitate the formation of stable metal complexes. Keeping this perspective in view, a new chelator, N, N′, N″-((1R, 3R)-cyclohexane-1, 3, 5-triyl)tris(8-hydroxyquinoline-2-carboxamide), TACH2COX, comprising of a cis, cis -1, 3, 5-trisaminocyclohexane(TACH) as central unit and three quinolinols joined through amide linkage is developed. The brown-colored ligand has been characterized through melting point, IR, NMR ( 1 H, 13 C), ESI mass, and absorption spectroscopy. The solution coordination chemistry of the newly synthesized ligand is studied by its interaction with three bio-relevant metal ions: iron(III), aluminum (III) and gallium(III) through spectroelectrochemical technique. The high metal–ligand formation constants of the ligand indicate that TACH2COX is one of the strong metal chelators amid synthetic chelators. The structure and bonding of the complexes have been established through DFT studies. The molecular modeling studies reveal that the tripodal ligand binds to the metal ions by coordination of the ligand through three sets of N, O-coordination sites on, each from one pendant showing distorted octahedral geometry. The NBO, EDA, ETS-NOCV analysis, and absorption spectra of the ligand and its metal complexes are also described.